2021
DOI: 10.3390/sym13101872
|View full text |Cite
|
Sign up to set email alerts
|

Disconnection between Rat’s Left and Right Hemisphere Impairs Short-Term Memory but Not Long-Term Memory

Abstract: Split-brain experiments, which have been actively conducted since the twentieth century, have provided a great deal of insight into functional asymmetry and inter-hemispheric interactions. However, how communication between the left and right hemispheres directly contributes to memory formation is still poorly understood. To address this issue, we cut the rat commissural fibers prior to performing behavioral tests, which consisted of two short-term and two long-term memory tasks. The result showed that cutting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…In rodents, in our previous work, we reported that lesions of the rat right hippocampus impaired short-term memory, while lesions of the left hippocampus impaired long-term memory [55]. We also reported results indicating that interhemispheric connections are necessary in short-term memory, but not in long-term memory, suggesting the existence of interhemispheric interactions [63]. Furthermore, according to the elegant experimental results by Shipton et al, "the optogenetic silencing of the left Cornu Ammonis 3 (CA3) alone impaired performance in the hippocampus-dependent long-term memory task, while the unilateral silencing of either the left or right CA3 caused short-term memory deficit in hippocampus-dependent tasks [58,64]" [63].…”
Section: Introductionsupporting
confidence: 53%
See 4 more Smart Citations
“…In rodents, in our previous work, we reported that lesions of the rat right hippocampus impaired short-term memory, while lesions of the left hippocampus impaired long-term memory [55]. We also reported results indicating that interhemispheric connections are necessary in short-term memory, but not in long-term memory, suggesting the existence of interhemispheric interactions [63]. Furthermore, according to the elegant experimental results by Shipton et al, "the optogenetic silencing of the left Cornu Ammonis 3 (CA3) alone impaired performance in the hippocampus-dependent long-term memory task, while the unilateral silencing of either the left or right CA3 caused short-term memory deficit in hippocampus-dependent tasks [58,64]" [63].…”
Section: Introductionsupporting
confidence: 53%
“…The rats were individually housed in cages with free access to food and water under a light-dark cycle, with the light period between 08:00 and 20:00 h. The rats were randomly assigned to the sham group, the right lesion group, the left lesion group, and the bilateral lesion group. All experiments were performed in accordance with the Guidelines for Animal Experiments at Doshisha University and with the approval of the Animal Research Committee of Doshisha University (approval code: A21007) [63].…”
Section: Animalsmentioning
confidence: 99%
See 3 more Smart Citations